A simple method for quantification of interferon-α2b through surface plasmon resonance technique - Ramanan, Ramakrishnan Nagasundara (Academic Journals, 2010)
A rapid and efficient immunoassay method for quantification of interferon-α2b using surface plasmon resonance was developed with BIAcore 3000 as a sensor. Two different levels of anti-interferon monoclonal antibody were immobilized onto a CM5 chip using an amine coupling method. Similar binding ratio was observed for both the ligand densities. There was no steric hindrance and loss of antibody activity even at higher ligand density (> 22,000 RU). The sensitivity of the assay was increased up to 45% with the increment in ligand density from 15,400 to 22,360 RU. The binding between interferon-α2b and anti-interferon monoclonal antibody was predominantly controlled by mass transfer rate and the relationship was found linear, ranged from 5 to 400 ng/mL. Total cycle time per analysis was less than 8 min and required only 5 μL of sample injection.